if I have too write (2/3,3) into a quadratic equation, how would I do so? Also how would I solve it?

So if (2/3,3) are the solution for a quadratic equation, then the quadratic expression should be factored by

(x-2/3) and (x-3).

Therefore the equation should be (x-2/3)(x-3)=0

x^2-2/3x-3x+(-2/3)*(-3)=0

x^2-11/3 x+2=0

3x^2-11x+6=0

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up